Numerical simulation of the Oncomelania snails transport attached to floating objects under different wind conditions - Zhang, Lin; Zhou, Jian-yin; Jin, Zhong-wu; Chai, Zhao-hui; Yang, Qi-hong (Frontiers in Ecology and Evolution, 2024)
The long-distance migration of Oncomelania snails mainly occurs by attaching to floating objects during floods. However, the processes, characteristics and effects of migration are not fully understood. Here, a motion equation for floating objects with attached Oncomelania snails was constructed using the Lagrangian method. The equation can be numerically solved to simulate the movement of floating objects after parameter calibration. An in situ experiment in the middle Changjiang (Yangtze) River was simulated to calibrate the turbulence diffusion coefficient. River flow information during the experiment was obtained by applying the MIKE3 model to simulate the water flow at that time. The wind speed was obtained from meteorological data. Then, the calibrated parameters were used to simulate the migration of Oncomelania snails in the lower Jingjiang River, where they had spread over a large area. The effects of flood conditions on the migration and spread of Oncomelania snails have been studied to a certain extent, but the impact of wind conditions on snail migration has rarely been reported. Therefore, based on the distribution of Oncomelania snails in China, the difficulties and key areas for the control of schistosomiasis and Oncomelania snails, and the morphological characteristics of the river reach, the Lower Jingjiang River section was selected as a practical application case. A theoretical model of the migration and spread of Oncomelania snails was established, and the characteristics of the Oncomelania snail migration were simulated and analyzed based on flood and distribution patterns under different wind conditions. This work advances previous qualitative descriptions of snail migration by including a quantitative model, and this research supports the control of snails and schistosomiasis based on its theoretical foundation and practical advances.